DESIGN AND OPTIMIZATION OF MICROPARTICULATE RESERVOIR MATRICES FOR COMBINATION THERAPY - YADAV, MANISH (International Journal of Applied Pharmaceutics, 2020)
Objective: The purpose of this investigation was to design and develop controlled release floating beads of Ketoprofenand Pantoprazole sodium. To determine the interaction between excipients used and to find out the nature of drug in the formulation, X-ray diffraction (XRD) and Differential Scanning Colorimetry (DSC) studies were performed. Methods: The beads were prepared by ionotropic gelation technique. Sodium alginate and HPMC E5LV was dissolved in deionized water (9:1 sodium alginate: HPMC E5LV) at a concentration of 1-3 % w/v using gentle heat on the water bath. After getting a clear solution, an accurately weighed quantity of Pantoprazole sodium was added and dispersed uniformly into the solution. In a separate beaker, Ketoprofen and calcium carbonate (1:1, Sodium alginate: CaCl2) was dispersed in water and mixed with sodium alginate solution containing Pantoprazole sodium. The bubble-free sodium alginate-drug dispersion (20 ml) was added dropwise via a 22-guage hypodermic needle fitted with a 10 ml syringe into 100 ml of calcium chloride solution (1-2 % w/v) containing 10 % glacial acetic acid and stirred at 400 rpm for 15 min. Results: From the experimental study, it was concluded that optimized batch F9 showed good micromeritic properties, entrapment efficiency and releases the drug slowly and completely for 12 h as beads remain in floating condition throughout dissolution study that assures prepared formulation remain floated in the stomach without its early passing to lower Gastro-Intestinal Tract(GIT) side. The percentage of drugs release of Ketoprofen and Pantoprazole Sodium was 96.56% and 97.74%, respectively at 12 h. Conclusion: Combination of different polymer provide sustained release pattern in different concentration. Formulation F9 gives good floating behavior using sodium alginate and HPMC hydroxypropyl methylcellulose in different ratios. In the present study, a satisfactory attempt has been made to formulate gastro retentive floating beads of Ketoprofen and Pantoprazole sodium.